(3aUd aj GdJhHIs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3GdMeO ddg aUd ai Cf GdJhHI hGdESJZaGQ jchf ef JQc GdhGLHGJ haYd GdeMQeGJ hGdChd jNai Ydi cKjQ ef GdfGS s
(3BNQgG (B:s
(3hbGd (B:" (3hcdhG hGTQHhG hdG JSQahG (B" (3aGdESQGa eLGhRI GdMO gPG BNQ eG cJHg gfG hGddg SHMGfg hJYGdi CYde hGdMeO ddg QH GdYGdejf JeJ HMeO Gddg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3Hg eWGdH ddcJGH HdZJ ebGHdI hJUMjMkG Ydi fSNI UMjMI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3Gdabg GdMfHdjs